Robotic versus open extended cholecystectomy for T1a–T3 gallbladder cancer: A matched comparison - Yang, Jun; Li, Enliang; Wang, Cong; Luo, Shuaiwu; Fu, Zixuan; Peng, Jiandong; Liao, Wenjun; Wu, Linquan (Frontiers in Surgery, 2022)
Background: The feasibility and safety of robotic extended cholecystectomy (REC) are still uncertain. This study was performed to compare the short- and long-term outcomes of REC with those of open extended cholecystectomy (OEC) for T1a-T3 gallbladder cancer. Methods: From January 2015 to April 2022, 28 patients underwent REC in our center. To minimize any confounding factors, a 1:2 propensity score-matching analysis was conducted based on the patients’ demographics, liver function indicators, T stage, and symptoms. The data regarding demographics, perioperative outcomes, and long-term oncologic outcomes were reviewed. Results: The visual analogue scale score was significantly lower in the REC than OEC group immediately postoperatively (3.68±2.09 vs. 4.73±1.85, P=0.008), on postoperative day 1 (2.96±1.75 vs. 3.69±1.41, P=0.023), and on postoperative day 2 (2.36±1.55 vs. 2.92±1.21, P=0.031). In addition, the REC group exhibited a shorter time to first ambulation (P=0.043), a shorter time to drainage tube removal (P=0.038), and a shorter postoperative stay (P=0.037). However, no statistically significant difference was found in the operation time (P=0.134), intraoperative blood loss (P=0.467), or incidence of postoperative morbidity (P=0.227) or mortality (P=0.289) between the REC and OEC groups. In regard to long-term outcomes, the 3-year disease-free survival rate was comparable between the OEC and REC groups (43.1% vs. 57.2%, P=0.684), as was the 3-year overall survival rate (62.8% vs. 75.0%, P=0.619). Conclusion: REC can be an effective and safe alternative to OEC for selected patients with T1a-T3 gallbladder cancer with respect to short- and long-term outcomes.